Answer:
Đặt \(A\left(x\right)=0\)
\(\Rightarrow\frac{2}{3}x^3+\frac{3}{4}x^2+\frac{4}{5}x-2\frac{13}{60}=0\)
\(\Rightarrow60\left(\frac{2}{3}x^3+\frac{3}{4}x^2+\frac{4}{5}x-\frac{133}{60}\right)=0.60\)
\(\Rightarrow40x^3+45x^2+48x-133=0\)
\(\Rightarrow40x^3+\left(85x^2-40x^2\right)+\left(133x-85x\right)-133=0\)
\(\Rightarrow\left(40x^3+85x^2+133x\right)-\left(40x^2+85x+133\right)=0\)
\(\Rightarrow x\left(40x^2+85x+133\right)-\left(40x^2+85x+133\right)=0\)
\(\Rightarrow\left(x-1\right)\left(40x+85x+133\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\40x^2+85x+133=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\x\in\varnothing\end{cases}}}\)